Pengaruh strategi pembelajaran REACT terhadap kemampuan berpikir kreatif dan komunikasi matematis - Komarudin, Komarudin; Mutia, Mutia; Putri, Dini Palupi; Masykur, Ruhban; Suherman, Suherman; Astuti, Amelia Dwi (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2022)
This study aims to examine the effect of the REACT learning strategy on the creative thinking and mathematical communication skills of MTs/SMP students. The population of this research is class VIII MTs Ma'arif NU 5 academic year 2021/2022, totaling 122 students. The sample used is class VIII A as the experimental class using the REACT learning strategy and class VIII C as the control class. Hypothesis testing using Multivariate Analysis of Variance or MANOVA. The prerequisite test is the normality test with the Kolmogrov-Smirnov test and the homogeneity test against the Box's test and the Levianate test. The results of data analysis showed that the so that was rejected, the then was rejected, the so was rejected. Based on this analysis and calculation, it is concluded that there is an effect of REACT learning strategy on students' creative thinking skills, there is an effect of REACT learning strategy on students' mathematical communication skills. In addition, there is an effect of REACT learning strategy on students' creative thinking and mathematical communication skills.